Acetaminophen / Tramadol Rectal Suppository for the Relief of Perineal Pain after Normal Vaginal Delivery: A randomized controlled trial - Chatwadee Pattarasiriwong; Densak Pongrojpaw; Athita Chanthasenanont; Supapen Lertwutwiwat; Kornkarn Bhamarapravatana; Komsun Suwannarurk (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives: To compare the effectiveness of acetaminophen /tramadol rectal suppository and placebo for pain relief after vaginal deliveryMaterials and Methods: Two hundred parturients who delivered vaginally were recruited. Twelve cases were excluded. Cases were randomly divided into two groups; study and control group. Acetaminophen/tramadol was given to the study group and placebo in control group immediately after vaginal delivery. Pain level was measured by visual analogue scale (VAS) at immediate, 6, 12 and 24 hours after delivery. Side effects and additional analgesic medication (acetaminophen) were recorded.Results: A total of 188 parturients were enrolled. Study and control groups consisted of 98 and 90 cases, respectively. Mean age of cases in this study was 27 years old. Forty percent of cases were nulliparous. All subjects were full term pregnancy with normal body mass index and equally demographic character. Pain score measured by VAS in both groups had no significant difference at all times (0, 6, 12 and 24 hours after delivery). There was no adverse event in this study.Conclusion: Acetaminophen/tramadol rectal suppository could not relieve perineal pain after normal vaginal delivery when comparing to placebo.